Mechanistic studies on isopenicillin n synthase - Abbott, S (1991)
The mechanism of penicillin formation through the action of the enzyme isopenicillin N synthase (IPNS) on the substrate δ-(L-α-aminoadipoyl)-L-cysteinyl-D-valine and synthetic analogues, still raises many unresolved questions, despite many years' extensive investigation. In order to investigate the stereochemistry of formation of the second ring in the product, N-δ-(L-α-aminoadipoyl)-3α-hydroxymethylpenicillin, resulting from incubation of δ-(L-α-aminoadipoyl)- L-cysteinyl-D-vinylglycine with IPNS, the deuterium labelled tripeptides δ-(L-α-aminoadipoyl)- L-cysteinyl-E-[3,4-2H2]-D-vinylglycine and δ-(L-α-aminoadipoyl)-L-cysteinyl- Z-[3,4-2H2]-D-vinylglycine were synthesised and incubated with recombinant IPNS. The pattern of deuterium labelling was retained in the penam products, indicating stereospecific ring closure. The unlabelled and labelled penicillins were converted to their corresponding γ-lactones, and the 1H NMR coupling constants for the C(3)H-C(8)H2 system used to assign the 8-Pro/? and 8-ProS resonances of the unlabelled lactone. Comparison with the labelled lactones indicated that the parent penicillins had been formed via syn addition of sulphur and oxygen across the double bonds of the respective tripeptides. This stereochemistry is consistent with a mechanism involving [2πs + 2π] cycloaddition of an Fe=O species to the olefln. [To continue reading the abstract please see the pdf]